Kamisama kiss. 25 - Suzuki, Julietta; Kimura, Tomo (VIZ Media, LLC, 2017)
The continuing adventures of Nanami Momozono and Tomoe and their efforts to stop Kirihito from reuniting Akura-oh's spirit with his body.